HUBUNGAN SIKAP PESERTA BIMBINGAN PERKAWINAN PRANIKAH TERHADAP NIAT MEMBINA KELUARGA SAKINAH - Ahmad Majidun (Wahana Islamika: Jurnal Studi Keislaman, 2018)
Pre-marital guidance for married age teenagers is importantto do, so the Ministry of Religion of Magelang Regency organizes theprogram in collaboration with Syubbanul Wathon Tegalrejo BoardingSchool. From the implementation of this activity, it is expected thatparticipants who take part in this program have knowledge about howto build a confident family. This knowledge can ultimately shape theattitudes of participants towards sakinah family development andultimately foster their intention to build a peaceful family. Thus thepurpose of this study is to analyze whether attitudes have a positiverelationship with the intention of fostering a healthy family. Theresearch sample was 100 respondents with a research questionnaire as adata collection tool. The data analysis used is Structural EquationModeling using SmarPLS software. The results of hypothesis testingprove that there is a positive and significant relationship betweenattitudes with the intention of participants to build a family with arelationship value of 0.529 or 52.9.